(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aimed to study vegetation change detection of Lattakia province by using remote sensing techniques, By applicating Normalized Differences Vegetation Index (NDVI) due to what these techniques had from quickly, accuracy, and completely. In addition to saving efforts and money. that change detection methods have showed by applicating it on Sentinel2 images the plant situation, it’s area and distribution in the studied area. In addition to knowing plant’s cover changes through time passing. Putting geo databases which benefit in knowing plant situation, and the periodicity supervision for it’s changes. The yearly and monthly changes of vegetation cover have been studied in Lattakia province, By making change detection for plants cover of march between (2016-2017). Then making change detection between march and august of 2017. It was observed that there were no big changes, Whether increasing or decreasing for plants cover when studying the yearly changes. While there was big decreasing of plants cover at western plain areas of province when studying the monthly changes between march and august due to raising of temperatures. And big increasing of vegetation in high areas.